Pola Asuh Anak Dengan Orang Tua Tunggal di Binamu Jeneponto - Aswar Ali Akbar (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
This study aims to find out (1) What is the pattern of parenting with single parents. (2) What factors support the care of children with single parents and (3) What factors inhibit the care of children with single parents. To achieve these objectives, the researchers used data collection techniques through documentation, observation, and interviews. Data obtained from the results of the study were processed using descriptive qualitative research methods. The results of the study show that (1) Parenting is applied by single parents in a variety of ways by single parents in teaching moral education to their children. Parenting applied by a single parent is almost the same as what he did above, but the difference is how to care for his child by much advising and teaching the meaning of life without a father and mother always giving motivation to their children to stay strong and study hard for the future what he aspires to. Parenting applied by single parents when educating children in learning tends to democratic parenting. This can be seen from the way single parents in guiding children's learning, they always support what children do related to learning activities, parenting that is applied is not strict, still firm but warm and full of understanding and affection and this single parent feels that which becomes (2) the supporting factor after separating from her husband is the closest person and the environment that provides motivation and enthusiasm and this single parent is quite comfortable with his status as a single parent even though his child sometimes looks for his father's figure. (3) Inhibiting factors for the father / mother in providing moral education to children, namely external and internal factors. Internal factors come from within the child's personal self. The inhibiting factor is the behavior of parents who are too harsh or authoritarian to children, low education of parents, too many rules and requests, busyness, limited time, economic factors and relationships that are less harmonious with children